1975
DOI: 10.4319/lo.1975.20.2.0198
|View full text |Cite
|
Sign up to set email alerts
|

Enewetak (Eniwetok) Atoll: Aspects of the nitrogen cycle on a coral reef1

Abstract: Changes in the concentrations of dissolved and particulate nitrogen in seawater crossing two interisland reef transects on Enewetak Atoll were measured. The upstream half of transect II consisted largely of algal pavement; the downstream half was visually dominated by corals. The other community, transect III, consisted of benthic algal covered pavement in its entirety, with only scattered small corals downstream. Both transects showed a significant net export of combined nitrogen, implying a large input of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 13 publications
(1 reference statement)
2
58
0
Order By: Relevance
“…In particular, sequences affiliated with the genus Nitrosopumilus dominated the archaeal communities in GBR ascidians and several Nitrosopumilus OTUs exhibited a widespread distribution among hosts and high relative abundance within hosts. In coral reef waters, observations of high nitrite/nitrate concentrations compared to adjacent, open water habitats have long suggested active nitrification among reefassociated microbes (Webb et al, 1975). More recent studies have reported that host-associated microbes in sponges and corals contributed to nitrification in these reef habitats to a larger extent than reported for free-living communities in sediments and seawater (Diaz and Ward, 1997;Southwell et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…In particular, sequences affiliated with the genus Nitrosopumilus dominated the archaeal communities in GBR ascidians and several Nitrosopumilus OTUs exhibited a widespread distribution among hosts and high relative abundance within hosts. In coral reef waters, observations of high nitrite/nitrate concentrations compared to adjacent, open water habitats have long suggested active nitrification among reefassociated microbes (Webb et al, 1975). More recent studies have reported that host-associated microbes in sponges and corals contributed to nitrification in these reef habitats to a larger extent than reported for free-living communities in sediments and seawater (Diaz and Ward, 1997;Southwell et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…unpubl.). Early atoll studies also documented N : P in incoming waters of 2 : 1 (Johannes et al 1972;Webb et al 1975), indicating that most reef systems are supplied with extremely N-poor waters, which makes them that much more N-limited (Odum and Odum 1955). Atkinson and Falter (2003) suggested that this missing nitrogen must come from either POM or nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in dissolved inorganic nutrient concentrations have been examined in a number of coral reef systems (Webb et al 1975;Crossland et al 1984;Miyajima et al 2007a); however, it has been difficult to evaluate how these ecosystem-scale changes reflect fluxes into and out of the individual communities that comprise the larger reef system. Comparatively few studies have quantified fluxes within natural reefs systems at the community scale (Crossland and Barnes 1983;Baird et al 2004;Cuet et al 2011a), largely due to the fact that uptake rates are often too slow to detect over smaller spatial scales (Atkinson and Smith 1987;Atkinson and Bilger 1992 Atkinson and Falter 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unimpacted coral reef communities exhibit relatively high gross productivity even though the surrounding waters contain low concentrations of nutrients; the net import of N and P is usually low to negligible and, in the case of N is often negative due to N-fixation (e.g., see Webb et al 1975;). The maintenance of this high gross productivity therefore requires high rates of supply of recycled nutrients.…”
Section: Eutrophication and Coral Reefsmentioning
confidence: 99%